2021
DOI: 10.1177/0271678x20980652
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arterial pulsatility is linked to hippocampal microvascular function and episodic memory in healthy older adults

Abstract: Microvascular damage in the hippocampus is emerging as a central cause of cognitive decline and dementia in aging. This could be a consequence of age-related decreases in vascular elasticity, exposing hippocampal capillaries to excessive cardiac-related pulsatile flow that disrupts the blood-brain barrier and the neurovascular unit. Previous studies have found altered intracranial hemodynamics in cognitive impairment and dementia, as well as negative associations between pulsatility and hippocampal volume. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…Resistance‐trained athletes may not be prone to orthostatic hypotension, showing an elevation in MAP during orthostatic stimulation (Sugawara et al., 2012). However, the greater blood flow pulsatility associated with a lower arterial compliance may affect the functional integrity of the brain (Palta et al., 2019) as well as cerebral microvascular function (Vikner et al., 2021). Despite these modality‐dependent cerebrovascular challenges, results from recent studies suggest no effect of exercise modality on dCA metrics derived from transfer function analysis (TFA) (Perry et al., 2019; Thomas et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance‐trained athletes may not be prone to orthostatic hypotension, showing an elevation in MAP during orthostatic stimulation (Sugawara et al., 2012). However, the greater blood flow pulsatility associated with a lower arterial compliance may affect the functional integrity of the brain (Palta et al., 2019) as well as cerebral microvascular function (Vikner et al., 2021). Despite these modality‐dependent cerebrovascular challenges, results from recent studies suggest no effect of exercise modality on dCA metrics derived from transfer function analysis (TFA) (Perry et al., 2019; Thomas et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These vascular changes may convey vulnerability to cerebral hypoperfusion injury (Sible et al, 2021b) and subsequent neuronal injury, especially in regions highly sensitive to BPrelated hypoxic-ischemic injury, such as the hippocampus (Iadecola, 2004;Ma et al,. 2020b;Vikner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: BPV = blood pressure variability et al, 2020), distending the arterial walls beyond repair and disrupting the tight junction of the blood-brain barrier. This effect may be especially pronounced in APOE ϵ4 carriers with genetic neurovascular vulnerability in smaller vascular compartments, where unsteady pulsatile forces may exacerbate a leaky blood-brain barrier (Vikner et al, 2021;Winder et al, 2021) and increase the risk for cerebral small vessel disease. It is striking that the current observations were made in a study sample with limited cerebrovascular disease (Hachinski Ischemic score ≤ 4).…”
mentioning
confidence: 99%
“…For example, the slope and amplitude of the pulse pressure wave may be related to intracranial compliance, with a less compliant tissue resulting in a steeper slope (Wagshul et al, 2011). A study in an older population used a high resolution 4D flow MRI measurement with velocity encoding sensitive to arterial blood flow speed to study the relation between the slope of the cardiac pulse in the cerebral arteries and episodic memory (Vikner et al, 2021). They found that steeper systolic onsets correlated with poorer episodic memory performance.…”
Section: Discussionmentioning
confidence: 99%